Study of some parameters of blood coagulation in patients with rheumatoid arthritis - Nuritdinova S. K. (Морфологія, 2010)
Rheumatoid arthritis represents one of actual problems of modern rheumatology. Disease is shown by symmetric defeat of joints, extraarticular changes, in pathogenesis of which leading part belong combined to shifts as a part of cellular and humoral immunity links. In the majority of works correlation between clinical features and indicators of coagulation system was not studied at rheumatoid arthritis. Aim: the studying of some indicators of blood curling system and their clinical- pathogenetic importance at patients with rheumatoid arthritis. Material and methods: In total there were examined 73 patients at the age from 21 till 60 years with duration of disease from 2 till 10 years, with diagnosis rheumatoid arthritis, which have been divided by degree of activity, stages RА, the articulate form and systemic manifestations. All patients with rheumatoid arthritis estimated a condition of coagulation system: defined thromboplastin-SI, activated partial thromboplastin time, fibrinogen, the international normalised relation. Results: at patients with rheumatoid arthritis there were increase of indicators of defined thromboplastin-SI, blood level of fibrinogen, decrease the international normalised relation, shortening the activated partial thromboplastin time that specifies the increasing of activity of coagulation system.